Nusselt number and friction factor correlation of solar air heater having winglet type vortex generator over absorber plate. (15th July 2020) - Kumar, Amit; Layek, Apurba
Highlights: An experimental work is done with Winglet type ribs placed on absorber plate of solar air heater. The plate temperature is evaluated through thermo-liquid crystal sheets or LCT sheet. The effect of relevant geometric parameters is examined. Regression analysis from the experimental data, correlations for Nusselt number ( Nu u ) and friction factor ( fr1 ) have been developed. Abstract: The experimentation has been done using the winglet type vortex generator as a roughness element above the absorber surface of a solar air heater (SAH) system. Different geometry-based roughness parameters have been considered such as relative roughness pitch (Pi /e) value of 5–12, relative roughness width (W w / w ) value of 3–7, angle of attack ( α ) value of 30 0 -75 0 and the flowing fluid Reynolds number diversified between 3000 and 22, 000 respectively and its effect on Nusselt number ( Nuu ) and friction factor ( fr1 ) were studied. In order to achieve its optimum condition, the Nusselt number ( Nuu ) and friction factor ( fr1 ) are analyzed for the roughness parameters to obtain the best overall performance and the required values are compared with the smooth type duct under similar flowing condition. Using regression analysis, correlations have been expanded for Nusselt number ( Nuu ) and friction component ( fr1 ) in terms of Reynolds number ( Re ) and with different parametric condition which is considered to be satisfactory when compared with the experimental results.